Analisis Perbandingan Jenis Material Penukar Kalor Plat Datar Aliran Silang Untuk Proses Pengeringan Kayu - Abeth Novria Sonjaya; Marhaenanto Marhaenanto; Mokhamad Eka Faiq; La Ode M Firman (Jurnal Teknologi, 2021)
The processed wood industry urgently needs a dryer to improve the quality of its production. One of the important components in a dryer is a heat exchanger. To support a durable heat transfer process, a superior material is needed. The aim of the study was to analyze the effectiveness of the application of cross-flow flat plate heat exchangers to be used in wood dryers and compare the materials used and simulate heat transfer on cross-flow flat plate heat exchangers using Computational Fluid Dynamic simulations. The results showed that there was a variation in the temperature out of dry air and gas on the flat plate heat exchanger and copper material had a better heat delivery by reaching the temperature out of dry air and gas on the flat plate type heat exchanger of successive cross flow and.   overall heat transfer coefficient value and the effectiveness value of the heat exchanger of the heat transfer characteristics that occur with the cross-flow flat plate type heat exchanger in copper material of 251.74725 W/K and 0.25.